Long-term efficacy, tolerability and overall survival in patients with platinum-sensitive, recurrent high-grade serous ovarian cancer treated with maintenance olaparib capsules following response to chemotherapy. Issue 9 (30th October 2018) - Friedlander, Michael; Matulonis, Ursula; Gourley, Charlie; du Bois, Andreas; Vergote, Ignace; Rustin, Gordon; Scott, Clare; Meier, Werner; Shapira-Frommer, Ronnie; Safra, Tamar; Matei, Daniela; Shirinkin, Vadim; et al.
Abstract Background In Study 19, maintenance monotherapy with olaparib significantly prolonged progression-free survival vs placebo in patients with platinum-sensitive, recurrent high-grade serous ovarian cancer. Methods Study 19 was a randomised, placebo-controlled, Phase II trial enrolling 265 patients who had received at least two platinum-based chemotherapy regimens and were in complete or partial response to their most recent regimen. Patients were randomised to olaparib (capsules; 400 mg bid) or placebo. We present long-term safety and final mature overall survival (OS; 79% maturity) data, from the last data cut-off (9 May 2016). Results Thirty-two patients (24%) received maintenance olaparib for over 2 years; 15 (11%) did so for over 6 years. No new tolerability signals were identified with long-term treatment and adverse events were generally low grade. The incidence of discontinuations due to adverse events was low (6%). An apparent OS advantage was observed with olaparib vs placebo (hazard ratio 0.73, 95% confidence interval 0.55‒0.95, P = 0.02138) irrespective ofBRCA1/2 mutation status, although the predefined threshold for statistical significance was not met. Conclusions Study 19 showed a favourable final OS result irrespective ofBRCA1/2 mutation status and unprecedented long-term benefit with maintenance olaparib for a subset of platinum-sensitive, recurrent ovarian cancer patients.